Growth Attributes and Economics of Brahmi (Bacopa monnieri L.) Cultivation Influenced by Organic Sources of Nutrients - Vikram, N.; Sarkar, N. C.; Sridhar, R.; Ghosh, B.; Doon, M. K.; Bochalya, K. S. (International Journal of Economic Plants, 2023)
A field study was conducted at the Agricultural Farm of Visva-Bharati University, Sriniketan, West Bengal, during August, 2021 to January, 2022 and August, 2022 to January, 2023 to evaluate the effects of different nutrient sources on Brahmi’s growth and profitability. Seven treatments were tested: T1 (NPK @ 50:25:25), T2 (farmyard manure @ FYM 10 t ha-1), T3 (vermicompost @ 5 t ha-1), T4 (FYM @ 10 t ha-1+ seaweed extract @ 3 ml l-1), T5 (vermicompost @ 5 t ha-1+seaweed extract @ 3 ml l-1), T6 (FYM @ 5 t ha-1+vermicompost @ 2.5 t ha-1), and T7 (control with no amendments). Growth parameters such as Leaf area index (LAI), crop growth rate (CGR), and relative growth rate (RGR) were recorded. Pooled data revealed that T6 (FYM+vermicompost) resulted in the highest LAI (1.536), CGR (1.462 g m-² day-1), and RGR (0.04338 g g-1 day-1), indicating its superior performance in promoting Brahmi’s growth. T6 also achieved the highest economic returns, with gross returns of ` 2,36,728 ha-1 and a benefit-cost ratio of 2.88, making it the most profitable treatment. Treatments T3 (vermicompost) and T5 (vermicompost+seaweed extract) also performed well, particularly during early growth stages, though they were outperformed by T6 over the entire growth cycle. T1 (NPK) and T2 (FYM) showed moderate growth and economic returns, while T7 (control) recorded the lowest performance in both growth indices and profitability. These findings underscore the effectiveness of organic amendments, particularly the combination of FYM and vermicompost, in enhancing both the growth and economic viability of Brahmi cultivation.